PERCEIVED TOURISM IMPACTS IN PINDUL CAVE, YOGYAKARTA, INDONESIA - Musadad Musadad; Nurlena Nurlena (Journal of Business on Hospitality and Tourism, 2016)
Gunungkidul Regency, Yogyakarta Province, Indonesia is experiencing significant increase in its visitors due to the massive development of its tourism objects, especially natural ones such as caves and beaches. Pindul Cave is one of the most prominent tourism object in Gunungkidul which is also visited by a high number of tourists although it was just opened in the late 2011s. Therefore, by conducting interviews with locals and the management as well as observation to collect data, this study investigated the perceived impacts of tourism in Pindul Cave. The analysis results show that the residents have positive attitudes towards socio-cultural, economic, and environmental impact although they also perceive negative impacts such as the way of employee’s recruitment by the management and the degradation of environment in the cave. However, these negative impacts are perceived minor by the residents so that, overall, they perceive that the development of tourism in Pindul Cave is positive.